Computational Fluid Dynamics Modeling of Proximal Landing Zones for Thoracic Endovascular Aortic Repair in the Bovine Arch Variant - Marrocco-Trischitta, Massimiliano M; Romarowski, Rodrigo M; Alaidroos, Moad; Sturla, Francesco; Glauber, Mattia; Nano, Giovanni (Annals of vascular surgery, 2020)
To assess the endograft displacement forces (DF), which quantify the forces exerted by the pulsatile blood flow on the vessel wall and transmitted on the terminal fixation site of the endograft after its deployment in proximal landing zones (PLZs) of the bovine aortic arch variant.BACKGROUNDTo assess the endograft displacement forces (DF), which quantify the forces exerted by the pulsatile blood flow on the vessel wall and transmitted on the terminal fixation site of the endograft after its deployment in proximal landing zones (PLZs) of the bovine aortic arch variant.Thirty healthy aortic computed tomographic angiographies of subjects with bovine arch configuration (10 per type of arch, I-III) were selected for the purpose of the study. A 3-dimensional model of the aortic arch lumen was reconstructed. Computational fluid dynamics modeling was then used to compute DF magnitude and orientation (i.e., x, y, and z axes) in PLZs of each case. DF values were normalized to the corresponding aortic wall area to estimate equivalent surface traction (EST).METHODSThirty healthy aortic computed tomographic angiographies of subjects with bovine arch configuration (10 per type of arch, I-III) were selected for the purpose of the study. A 3-dimensional model of the aortic arch lumen was reconstructed. Computational fluid dynamics modeling was then used to compute DF magnitude and orientation (i.e., x, y, and z axes) in PLZs of each case. DF values were normalized to the corresponding aortic wall area to estimate equivalent surface traction (EST).DF were highest in zone 0, consistently with the greater surface area. DF in zone 3 were much greater than in zone 2 because of a 3-fold greater upward component (z axis) (P < 0.001), being therefore mainly oriented orthogonally to the aortic blood flow and to the vessel longitudinal axis in that zone. EST progressively increased from zone 0 toward more distal PLZs, with EST in zone 3 being much greater than that in zone 2 (P < 0.001). The same pattern was observed after stratification by type of arch.RESULTSDF were highest in zone 0, consistently with the greater surface area. DF in zone 3 were much greater than in zone 2 because of a 3-fold greater upward component (z axis) (P < 0.001), being therefore mainly oriented orthogonally to the aortic blood flow and to the vessel longitudinal axis in that zone. EST progressively increased from zone 0 toward more distal PLZs, with EST in zone 3 being much greater than that in zone 2 (P < 0.001). The same pattern was observed after stratification by type of arch.The bovine arch is associated with a consistent fluid dynamic pattern, which identifies in zone 3 an unfavorable biomechanical environment for endograft deployment.CONCLUSIONSThe bovine arch is associated with a consistent fluid dynamic pattern, which identifies in zone 3 an unfavorable biomechanical environment for endograft deployment.